toner

JP7638738B2Active Publication Date: 2025-03-04CANON KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021040525
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-12
Publication Date
2025-03-04
Estimated Expiration
2041-03-12

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、低温定着性に優れ、印刷画像の経時でのグロス変化を抑えるトナーを得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638738000001
    Figure 0007638738000001
  • Figure 0007638738000002
    Figure 0007638738000002
  • Figure 0007638738000003
    Figure 0007638738000003
Patent Text Reader

Abstract

To provide a toner that is excellent in low temperature fixability and suppress a change in gloss over time of a print image.SOLUTION: A toner has a toner particle containing a binder resin, a crystalline material A, and a crystalline material B. The binder resin contains a resin M in an amount of 70 mass% or more based on a mass of the binder resin. A melting point of the crystalline material A is 50.0°C or more and 100.0°C or less. When an absolute value of a difference in a SP value between the resin M and the crystalline material A is ΔSPAM, an absolute value of a difference in the SP value between the resin M and the crystalline material B is ΔSPBM, an absolute value of a difference in the SP value between the crystalline material A and the crystalline material B is ΔSPAB, peak molecular weight Mp of the crystalline material A is MpA, and peak molecular weight Mp of the crystalline material B is MpB, following formulas (1)-(3) are satisfied. (1) 50≤MpB×ΔSPBM2-MpA×ΔSPAM2≤450; (2) MpA×ΔSPAM2≤800; (3) ΔSPAB≤0.26.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE This disclosure relates to toners for use in imaging processes such as electrophotography. [Background technology]

[0002] In recent years, further reduction in power consumption has been demanded in electrophotographic image forming apparatuses such as multifunction machines and printers. In electrophotography, first, an electrostatic latent image is formed on an electrophotographic photoreceptor (image carrier) through charging and exposure processes. Next, the electrostatic latent image is developed with a developer containing a toner, and a visualized image (fixed image) is obtained through a transfer process and a fixing process. Among the above processes, the fixing process requires a relatively large amount of energy, and from the viewpoint of reducing power consumption, reduction in the amount of heat applied to the fixing device in particular has been considered. With regard to toner, there is an increasing need for so-called low-temperature fixing toner that can be fixed with less heat.

[0003] In Patent Document 1, an ester wax having a specific structure and physical properties and a wax having a specific heat absorbing property are added to a binder resin or toner. Furthermore, it is proposed to improve the low temperature fixing performance and offset resistance of the toner by setting the weight average particle size of the toner particles within a specific range.

[0004] In addition, in Patent Document 2, a specific diester compound is used as a softener, and the softening temperature, flow start temperature, and glass transition temperature of the toner are controlled within specific ranges, respectively, thereby proposing to obtain a toner that has excellent low-temperature fixing properties and imparts high gloss (glossy feel) to printed matter over a wide temperature range. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-133412 [Patent Document 2] International Publication No. 2013 / 047296 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned patent documents do not mention the storage stability of images printed using the obtained toner, and no experimental results are given. When a crystalline plasticizer is added to a toner as in the toners described in these documents, the low-temperature fixing property is certainly improved. While the plasticizing effect of the crystalline plasticizer increases depending on the amount of the plasticizer added, the storage stability of the printed image tends to decrease when the amount of the plasticizer added is increased. Specifically, in a printed image left in a high-temperature environment, the plasticizer gradually crystallizes, causing a change in the uneven shape of the image surface, resulting in a detrimental effect of decreasing the image gloss over time.

[0007] That is, even when the toners described in these documents are used, it has been found that there are still problems in terms of achieving both low-temperature fixability and print image storage stability. The present disclosure provides a toner that achieves both low-temperature fixability and print image storage stability at a high level. Specifically, the present disclosure provides a toner that has excellent low-temperature fixability and suppresses gloss change over time in a printed image. [Means for solving the problem]

[0008] The present disclosure relates to Binder resin, crystalline material A、 Crystalline material B and crystalline material C A toner having toner particles comprising The binder resin contains 70% by mass or more of resin M based on the mass of the binder resin, The melting point of the crystalline material A is 50.0°C or more and 100.0°C or less, the content of the crystalline material A relative to the total amount of the crystalline materials in the toner is 56% by mass or more; The absolute value of the SP value difference between the resin M and the crystalline material A is ΔSPAM (cal / cm 3 ) 1 / 2 year, The absolute value of the SP value difference between the resin M and the crystalline material B is ΔSPBM (cal / cm 3) 1 / 2 year, The absolute value of the SP value difference between the resin M and the crystalline material C is ΔSPCM (cal / cm 3 ) 1 / 2 year, The absolute value of the SP value difference between the crystalline material A and the crystalline material B is ΔSPAB (cal / cm 3 ) 1 / 2 year, The peak molecular weight Mp of the crystalline material A is designated as MpA, and the peak molecular weight Mp of the crystalline material B is designated as MpB. The peak molecular weight Mp of the crystalline material C is designated as MpC. When I did, The following formulas (1) to ( 5 ) toner. 50≦MpB×ΔSPBM 2 -MpA×ΔSPAM 2 ≦450 (1) MpA×ΔSPAM 2 ≦800 (2) ΔSPAB≦0.26 (3) 0 <MpC×ΔSPCM 2 -MpB × ΔSPBM 2 ···(4) 800 <MpC×ΔSPCM 2 ···(5) Effect of the Invention

[0009] According to the present disclosure, it is possible to obtain a toner that has excellent low-temperature fixing properties and suppresses gloss change over time in printed images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined.

[0011] As mentioned above, when a crystalline plasticizer is added to a toner, the low-temperature fixing property improves depending on the amount of plasticizer added, but the printed image after being left in a high-temperature environment has a detrimental effect of decreasing gloss. This is believed to be because the plasticizer gradually crystallizes on the surface of the printed image, causing changes in the unevenness of the image surface.

[0012] The present inventors have studied a method for suppressing such adverse effects caused by crystalline plasticizers. They believe that the gradual crystallization of the plasticizer on the surface of the printed image is due to insufficient recrystallization of the plasticizer after fixing. However, plasticizers that are prone to recrystallization after fixing have low compatibility with the binder resin and tend not to provide sufficient plasticizing effect. On the other hand, if a plasticizer with high compatibility with the binder resin is selected to obtain a sufficient plasticizing effect, recrystallization after fixing tends to be insufficient. The present inventors have found a method for obtaining a high plasticizing effect on the binder resin and quickly recrystallizing the image after fixing by using two materials, crystalline material A and crystalline material B, in addition to the binder resin. Specifically, they have found that the above problem can be solved by the following toner.

[0013] A toner having toner particles containing a binder resin, a crystalline material A and a crystalline material B, The binder resin contains 70% by mass or more of resin M based on the mass of the binder resin, The melting point of the crystalline material A is 50.0°C or more and 100.0°C or less, The absolute value of the SP value difference between the resin M and the crystalline material A is ΔSPAM, The absolute value of the SP value difference between the resin M and the crystalline material B is ΔSPBM, The absolute value of the SP value difference between the crystalline material A and the crystalline material B is ΔSPAB, When the peak molecular weight Mp of the crystalline material A is MpA and the peak molecular weight Mp of the crystalline material B is MpB, A toner that satisfies the following formulas (1) to (3). 50≦MpB×ΔSPBM 2 -MpA×ΔSPAM 2 ≦450 (1) MpA×ΔSPAM2 ≦800 (2) ΔSPAB≦0.26 (3)

[0014] The toner particles contain a resin M, a crystalline material A, and a crystalline material B. Here, the crystalline material is a compound in which an endothermic peak is observed in differential scanning calorimetry (DSC).

[0015] Crystalline material A exhibits a sufficient plasticizing effect on resin M, the main component of the binder resin, but is a material that does not easily recrystallize after fixing. Crystalline material B exhibits a smaller plasticizing effect than crystalline material A, but is a material that easily recrystallizes after fixing. When the structural similarity between these two materials, crystalline material A and crystalline material B, satisfies certain conditions, it becomes possible to achieve both a high plasticizing effect on the binder resin and ease of recrystallization after fixing. In other words, by having crystalline material B, which exhibits an excellent nucleating agent effect, act as a crystal nucleating agent for crystalline material A, which exhibits an excellent plasticizing effect, a toner that has excellent low-temperature fixing properties and suppresses gloss changes over time in printed images can be obtained.

[0016] The χ parameter is considered as an index of compatibility between two materials such as a binder resin and a plasticizer. This χ parameter is proportional to the product of the square of the difference in the SP values ​​of the two materials and the peak molecular weight Mp of the plasticizer. It is known from the Flory-Huggins theory that the smaller the value of the χ parameter, the higher the compatibility between the two materials. In general, it is known that a crystalline material that is highly compatible with a binder resin exhibits an excellent plasticizing effect. In the above formula, the index of the plasticity of the crystalline material with respect to the binder resin is the square of the difference in the SP values ​​of the crystalline material and the resin M, which is the main component of the binder resin, multiplied by the peak molecular weight Mp of the crystalline material.

[0017] The SP value, also known as the solubility parameter, is a number used as an index of solubility and affinity, showing how much a substance dissolves in another substance. Materials with similar SP values ​​have high solubility and affinity, while materials with different SP values ​​have low solubility and affinity.

[0018] The SP value can be calculated by the Fedor method, which is described in detail in, for example, Polymer Engineering and Science, Vol. 14, pages 147-154, and the SP value can be calculated by the following formula. Formula: SP value = √(Ev / v) = √(ΣΔei / ΣΔvi) (Wherein, Ev: evaporation energy (cal / mol), v: molar volume (cm 3 / mol), Δei: evaporation energy of each atom or atomic group, Δvi: molar volume of each atom or atomic group)

[0019] In the above toner, when the absolute value of the SP value difference between resin M and crystalline material A is ΔSPAM, the absolute value of the SP value difference between resin M and crystalline material B is ΔSPBM, the absolute value of the SP value difference between crystalline material A and crystalline material B is ΔSPAB, the peak molecular weight Mp of crystalline material A is MpA, and the peak molecular weight Mp of crystalline material B is MpB, it is necessary to satisfy the following formula (1). 50≦MpB×ΔSPBM 2 -MpA×ΔSPAM 2 ≦450 (1) The first term in the middle of formula (1) is the peak molecular weight MpB of crystalline material B multiplied by the square of the absolute value of the difference in SP value between resin M and crystalline material B.

[0020] That is, the first term in the middle of formula (1) is a term that represents the compatibility between crystalline material B and resin M, and the second term in the middle of formula (1) is a term that represents the compatibility between crystalline material A and resin M. Therefore, the middle term of formula (1) represents a comparison of the compatibility between crystalline material A and crystalline material B and resin M. For the toner, it is necessary to use two types of crystalline materials that differ in compatibility with resin M, which is the main component of the binder resin. A crystalline material A that has high compatibility with resin M and a crystalline material B that has lower compatibility with resin M than A are used in combination.

[0021] Formula (1) indicates that the compatibility between crystalline material A and resin M is greater than the compatibility between crystalline material B and resin M, and the difference must be 50 or more and 450 or less. If the middle side of formula (1) is smaller than 50, the difference in compatibility between crystalline material A and crystalline material B with the binder is insufficient, and the effect of crystalline material B in promoting the recrystallization of crystalline material A on the fixed image becomes insufficient. As a result, a decrease in gloss is likely to occur in the printed image after it is left in a high-temperature environment.

[0022] On the other hand, when the middle side of formula (1) is larger than 450, the crystalline material A and the crystalline material B are separated in the binder resin on the fixed image, and the gloss of the printed image is likely to decrease after being left in a high-temperature environment. 2 -MpA×ΔSPAM 2 is preferably 100-440, more preferably 150-430.

[0023] In the above toner, it is necessary to satisfy the following formula (2). MpA×ΔSPAM 2 ≦800 (2) The left side of formula (2) indicates the compatibility between crystalline material A and resin M. The left side of formula (2) must be 800 or less. By being 800 or less, an excellent plasticizing effect on the binder resin can be obtained. If it is more than 800, the compatibility of crystalline material A with resin M becomes insufficient and the plasticizing effect cannot be obtained. As a result, the low-temperature fixability decreases. MpA×ΔSPAM 2 is preferably 700 or less, more preferably 600 or less. There is no particular lower limit, but it is preferably 150 or more, more preferably 350 or more.

[0024] In the above toner, it is necessary to satisfy the following formula (3). ΔSPAB≦0.26 (3) ΔSPAB indicates the absolute value of the difference in SP value between crystalline material A and crystalline material B, and indicates the affinity and structural similarity between crystalline material A and crystalline material B.

[0025] It is necessary that the absolute difference in SP value between crystalline material A and crystalline material B is 0.26 or less. When it is 0.26 or less, the structural similarity between crystalline material A and crystalline material B is sufficiently close, and the effect of recrystallizing crystalline material A by crystalline material B is obtained. When it is more than 0.26, crystalline material A and crystalline material B become difficult to mix, and gloss reduction is likely to occur in the printed image after being left in a high temperature environment. ΔSPAB is preferably 0.17 or less, more preferably 0.12 or less. The lower limit is not particularly limited, but is preferably 0.00 or more, more preferably 0.01 or more.

[0026] In addition to crystalline materials A and B, the toner particles preferably contain a crystalline material C that satisfies the following characteristics: That is, when the absolute value of the SP value difference between resin M and crystalline material C is ΔSPCM and the peak molecular weight of crystalline material C is MpC, the toner particles preferably contain a crystalline material C that satisfies the following formulas (4) and (5): 0 <MpC×ΔSPCM 2 -MpB × ΔSPBM 2 (4) 800 <MpC×ΔSPCM 2 (5)

[0027] Formula (4) indicates that the compatibility of crystalline material C with resin M is lower than that of crystalline material B with resin M. Furthermore, formula (5) indicates that the compatibility of crystalline material C with resin M is low, and that crystalline material C is easily crystallized after melting with resin M. By satisfying formulas (4) and (5), the effect of crystalline material C promoting the recrystallization of crystalline material B on the fixed image is easily obtained. As a result, gloss loss is suppressed in the printed image after it is left in a high-temperature environment.

[0028] MpC × ΔSPCM 2 -MpB × ΔSPBM 2 It is more preferable that the number is 100 or more. It is more preferable that MpC×ΔSPCM is 150 or more. 2 -MpB × ΔSPBM 2The upper limit of MpC×ΔSPCM is not particularly limited, but is preferably 600 or less, and more preferably 500 or less. 2 is preferably 900 or more, and more preferably 1000 or more. 2 The upper limit is not particularly limited, but is preferably 1300 or less, and more preferably 1200 or less.

[0029] In addition, when the absolute value of the SP value difference between crystalline material B and crystalline material C is ΔSPBC, it is preferable that the following formula (6) is satisfied. 0 < ΔSPCM - ΔSPBC (6)

[0030] Formula (6) shows that the structural similarity between crystalline material B and crystalline material C is higher than that between crystalline material C and resin M. In such a case, crystalline material C is easy to recrystallize and has better affinity with crystalline material B than with the binder resin. By including such crystalline material C in the toner particles, the recrystallization of crystalline material B is promoted. Furthermore, by satisfying the above-mentioned relationship between crystalline material A and crystalline material B, the recrystallization of crystalline material A is promoted. As a result, it is possible to achieve both good low-temperature fixing property and suppression of gloss change of the toner after fixing at an even higher level. ΔSPCM-ΔSPBC is more preferably 0.80 or more, and even more preferably 0.90 or more. The upper limit is preferably 1.25 or less, and more preferably 1.10 or less.

[0031] In addition, when the absolute value of the SP value difference between crystalline material A and crystalline material C is ΔSPAC, it is preferable that the following formula (7) is satisfied. 0 < ΔSPAC-ΔSPBC (7) This means that crystalline material C and crystalline material B are more compatible than crystalline material C and crystalline material A. When formula (7) is satisfied, the effect of crystalline material C promoting the crystallization of crystalline material B on the fixed image and the effect of crystalline material B promoting the crystallization of crystalline material A are enhanced. As a result, gloss reduction is suppressed in the printed image after being left in a high-temperature environment. ΔSPAC-ΔSPBC is more preferably 0.01 or more, and even more preferably 0.02 or more. The upper limit is preferably 0.30 or less, and more preferably 0.12 or less.

[0032] [About binder resin and resin M] The binder resin contains 70% by mass or more of resin M based on the total amount of the binder resin. Resin M is preferably an amorphous resin. The content of resin M based on the total amount of the binder resin is more preferably 80% by mass or more, and even more preferably 90% by mass or more. There is no particular upper limit, but it is preferably 100% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less.

[0033] Preferred examples of the binder resin and its main component resin M include vinyl resins and polyester resins. Examples of the vinyl resins, polyester resins and other binder resins include the following resins or polymers: homopolymers of styrene and its substitutes, such as polystyrene and polyvinyltoluene; styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; styrene-based copolymers, such as polymethyl methacrylate, polybutyl methacrylate, and the like. Acrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyamide resin, epoxy resin, polyacrylic resin, rosin, modified rosin, terpene resin, phenolic resin, aliphatic or alicyclic hydrocarbon resin, aromatic petroleum resin. These binder resins can be used alone or in combination.

[0034] The binder resin and resin M preferably contain a carboxy group, and more preferably are vinyl resins having a carboxy group. The binder resin having a carboxy group can be produced, for example, by using a polymerizable monomer that produces a desired binder resin in combination with a polymerizable monomer that contains a carboxy group.

[0035] Examples of the polymerizable monomer containing a carboxy group include vinylic carboxylic acids such as acrylic acid, methacrylic acid, α-ethylacrylic acid, and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid, and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives such as succinic acid monoacryloyloxyethyl ester, succinic acid monomethacryloyloxyethyl ester, phthalic acid monoacryloyloxyethyl ester, and phthalic acid monomethacryloyloxyethyl ester.

[0036] For example, the following monomers can be used for the vinyl resin: styrene monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, p-phenylstyrene, p-chlorostyrene, 3,4-dichlorostyrene, p-ethylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene, and acrylic esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, propyl acrylate, n-octyl acrylate, dodecyl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, and phenyl acrylate. Methacrylic acid esters such as α-methylene aliphatic monocarboxylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, dodecyl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate, and diethylaminoethyl methacrylate.

[0037] Among these, the resin M is preferably a vinyl resin, and more preferably a polymer of a monomer containing at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters and styrene. The vinyl resin is a polymer or copolymer of a compound containing a group having an ethylenically unsaturated bond such as a vinyl group. Examples of the group having an ethylenically unsaturated bond include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group.

[0038] The binder resin preferably contains the other resins described above as the binder resin in addition to the resin M. As the other resins, the binder resin preferably contains at least one selected from the group consisting of an amorphous polyester resin and polystyrene. The content of the other resins in the binder resin is preferably 2% by mass to 30% by mass, more preferably 2% by mass to 20% by mass, and further preferably 3% by mass to 10% by mass.

[0039] The polyester resin may be a condensation polymer of the following carboxylic acid component and alcohol component. The carboxylic acid component may be terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid, and trimellitic acid. The alcohol component may be bisphenol A, hydrogenated bisphenol A, or the like. Examples of the monomers that can be used include ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, glycerin, trimethylolpropane, and pentaerythritol.

[0040] The polyester resin may also be a polyester resin containing a urea group. It is preferable that the carboxyl group at the terminal of the polyester resin is not capped. The binder resin and the resin M may have a polymerizable functional group for the purpose of improving the viscosity change of the toner at high temperatures. Examples of the polymerizable functional group include a vinyl group, an isocyanate group, an epoxy group, an amino group, a carboxyl group, and a hydroxyl group.

[0041] The weight average molecular weight Mw of the resin M is preferably 20,000 or more and 40,000 or less, and more preferably 25,000 or more and 35,000 or less.

[0042] [About crosslinking agents] In order to control the molecular weight of the binder resin constituting the toner particles, a crosslinking agent may be added during polymerization of the polymerizable monomer. The resin M is preferably a polymer of at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters, styrene, and a crosslinking agent.

[0043] For example, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, and #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester diacrylate (MANDA Nippon Kayaku), and those in which the above acrylates have been replaced with methacrylates. The amount of the crosslinking agent added is preferably 0.001 parts by mass or more and 15,000 parts by mass or less based on 100 parts by mass of the polymerizable monomer.

[0044] [Crystalline material A] The crystalline material A will be described. The crystalline material A is not particularly limited as long as it satisfies the above-mentioned formulas (1) to (3), and in addition to known waxes, known crystalline resins such as crystalline polyesters, crystalline vinyl resins, crystalline polyurethanes, and crystalline polyureas can be used.

[0045] The melting point of the crystalline material A is 50.0°C or more and 100.0°C or less. When the melting point of the crystalline material A is in the above range, both low-temperature fixability and storage stability of the toner can be achieved. When the melting point of the crystalline material A is 50.0°C or more, the storage stability of the fixed image at high temperatures is improved. Furthermore, when the melting point is 100.0°C or less, sufficient low-temperature fixability can be obtained. The melting point of the crystalline material A is preferably 60.0°C or more and 100.0°C or less, more preferably 60.0°C or more and 90.0°C or less, and even more preferably 63.0°C or more and 85.0°C or less. The melting point of the crystalline material A can be controlled by the constituent materials of the crystalline material A. A method for measuring the melting point of the crystalline material A will be described later.

[0046] Crystalline material A was measured by high temperature gel permeation chromatography (GPC). The peak molecular weight (Mp) of the o-dichlorobenzene soluble matter is preferably 400 or more and 2000 or less. When the peak molecular weight (Mp) is 400 or more, the storage stability of the toner is less likely to decrease. Furthermore, when the peak molecular weight is 2000 or less, the plasticity to the binder resin is high and the low-temperature fixing property is further improved. More preferably, the peak molecular weight is 500 or more and 1000 or less, and even more preferably, the peak molecular weight is 500 or more and 800 or less. The method for measuring the peak molecular weight of the crystalline material A will be described later.

[0047] The crystalline material A must be selected within a range that satisfies formula (2) from the viewpoint of compatibility with the binder resin. The preferred material varies depending on the resin M used, but wax is preferred because it has a wide range of material options.

[0048] Specific examples of the wax include monofunctional ester waxes such as behenyl behenate, stearyl stearate, palmityl palmitate, and the like; bifunctional ester waxes such as dibehenyl sebacate, hexanediol dibehenate, and the like; trifunctional ester waxes such as glycerin tribehenate, and the like; tetrafunctional ester waxes such as pentaerythritol tetrastearate, pentaerythritol tetrapalmitate, and the like; hexafunctional ester waxes such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and the like; polyfunctional ester waxes such as polyglycerin behenate, and the like; natural ester waxes such as carnauba wax, rice wax, and the like; petroleum waxes and derivatives thereof such as paraffin wax, microcrystalline wax, petrolatum, and the like; hydrocarbon waxes and derivatives thereof produced by the Fischer-Tropsch method; polyolefin waxes and derivatives thereof such as polyethylene wax, polypropylene wax, and the like; higher aliphatic alcohols; fatty acids such as stearic acid, palmitic acid, and the like; and acid amide waxes.

[0049] Among them, ester waxes which are condensates of alcohol components and carboxylic acid components are preferred, and monofunctional ester waxes and bifunctional ester waxes are particularly preferred. Among these waxes, it is preferred to use a bifunctional ester wax (diester) having two ester bonds in the molecular structure.

[0050] The difunctional ester wax is an ester compound of a dihydric alcohol and an aliphatic monocarboxylic acid, or an ester compound of a dihydric carboxylic acid and an aliphatic monoalcohol.

[0051] Specific examples of aliphatic monocarboxylic acids include myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, etc. Specific examples of aliphatic monoalcohols include myristyl alcohol, cetanol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, triacontanol, etc.

[0052] Specific examples of divalent carboxylic acids include butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), heptanedioic acid (pimelic acid), octanedioic acid (suberic acid), nonanedioic acid (azelaic acid), decanedioic acid (sebacic acid), dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0053] Specific examples of dihydric alcohols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, and 1,18-octadecane. Examples of the monomers include diol, 1,20-eicosanediol, 1,30-triacontanediol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiroglycol, 1,4-phenylene glycol, bisphenol A, and hydrogenated bisphenol A.

[0054] More specifically, the crystalline material A is preferably a condensate (bifunctional ester wax) of an aliphatic diol having 2 to 10 carbon atoms and an aliphatic monocarboxylic acid having 14 to 24 carbon atoms, and more preferably a condensate (bifunctional ester wax) of an aliphatic diol having 2 to 6 carbon atoms and an aliphatic monocarboxylic acid having 14 to 22 carbon atoms. Examples of the diol having 2 to 6 carbon atoms include ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol. Examples of the aliphatic monocarboxylic acid having 14 to 24 carbon atoms include myristic acid, palmitic acid, stearic acid, and behenic acid. Furthermore, ethylene glycol distearate, which is an ester compound of ethylene glycol and stearic acid, is particularly preferred.

[0055] The carbon number of the diol component of the ester compound and the carbon number of the monocarboxylic acid can be determined by analyzing the toner particles with pyrolysis GC / MS. If necessary, the analysis can be made easier by performing derivatization in advance using a methylating agent or the like.

[0056] Methods for producing a diester compound include synthesis by oxidation reaction, synthesis from carboxylic acid and its derivatives, ester group introduction reaction represented by Michael addition reaction, a method utilizing a dehydration condensation reaction from a carboxylic acid compound and an alcohol compound, a reaction from an acid halide and an alcohol compound, an ester exchange reaction, etc. A catalyst can also be used appropriately.

[0057] As the catalyst, a general acidic or alkaline catalyst used in an esterification reaction, such as zinc acetate or a titanium compound, is preferred. After the esterification reaction, the target product may be purified by recrystallization, distillation, or the like. A representative production example is as follows. However, the production method of the diester compound used in the present invention is not limited to the following.

[0058] First, the raw material alcohol and carboxylic acid are added to a reaction vessel. For example, the alcohol and carboxylic acid are mixed so that the molar ratio is diol:monocarboxylic acid=1:2 or monoalcohol:dicarboxylic acid=2:1. The ratio may be changed in consideration of the reactivity in the dehydration condensation reaction. Next, the mixture is appropriately heated to carry out the dehydration condensation reaction. A basic aqueous solution and an appropriate organic solvent are added to the esterification crude product obtained by the dehydration condensation reaction, and the unreacted alcohol and carboxylic acid are deprotonated and separated into the aqueous phase. After that, a diester compound is obtained by appropriately washing with water, distilling off the solvent, and filtering.

[0059] The content of the crystalline material A is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, and even more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the binder resin. The content of the crystalline material A in the total amount of the crystalline material is preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more. There is no particular upper limit, but it is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less.

[0060] [About crystalline material B] Next, the crystalline material B will be described. The crystalline material B is not particularly limited as long as it satisfies the above-mentioned formulas (1) and (3), and in addition to known waxes, known crystalline materials such as crystalline polyester, crystalline vinyl resin, crystalline polyurethane, and crystalline polyurea can be used. A known crystalline resin can be used. A preferred material varies depending on the resin M and the crystalline material A that are the main components of the binder resin, but may be selected from the viewpoints of compatibility with the resin M and structural similarity with the crystalline material A. Specifically, a material that has lower compatibility with the resin M compared to the crystalline material A and has high structural similarity with the crystalline material A should be selected so as to satisfy formulas (1) and (3).

[0061] When the crystalline material A is an ester wax, it is preferable that the crystalline material B is an ester wax. In addition, examples of preferable materials include the following: esters of monohydric alcohols and aliphatic carboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate, or esters of monohydric carboxylic acids and aliphatic alcohols; esters of dihydric alcohols and aliphatic carboxylic acids, such as dibehenyl sebacate, or esters of dihydric carboxylic acids and aliphatic alcohols.

[0062] Crystalline material B is more preferably a condensate (bifunctional ester wax) of an aliphatic dicarboxylic acid having 2 to 10 carbon atoms and an aliphatic monoalcohol having 14 to 24 carbon atoms, and even more preferably a condensate (bifunctional ester wax) of an aliphatic dicarboxylic acid having 6 to 10 carbon atoms and an aliphatic monoalcohol having 14 to 22 carbon atoms.

[0063] The melting point of crystalline material B is preferably 50°C or higher and 100°C or lower. When the melting point of crystalline material B is within the above range, it becomes easy to achieve both low-temperature fixability and storage stability of the toner. The melting point of crystalline material B is more preferably 60°C or higher and 100°C or lower, even more preferably 60°C or higher and 90°C or lower, and even more preferably 70°C or higher and 85°C or lower. The melting point of crystalline material B can be controlled by the constituent materials of crystalline material B. A method for measuring the melting point of crystalline material B will be described later.

[0064] The crystalline material B preferably has a peak molecular weight (Mp) of o-dichlorobenzene soluble matter of 400 or more and 2000 or less, as measured by high-temperature gel permeation chromatography (GPC). When the peak molecular weight (Mp) is 400 or more, the storage stability of the toner is less likely to decrease. Furthermore, when the peak molecular weight is 2000 or less, the low-temperature fixing property is less likely to decrease. The peak molecular weight (Mp) is more preferably 500 or more and 1000 or less. The method for measuring the peak molecular weight of the crystalline material B will be described later.

[0065] The content of crystalline material B is preferably less than the content of crystalline material A. In other words, when the content of crystalline material A in the toner is XA (mass%) and the content of crystalline material B in the toner is XB (mass%), it is preferable that the following formula (8) is satisfied. XA-XB>0 (8) This is because crystalline material A acts on resin M, which is the main component of the binder resin, while crystalline material B acts mainly on crystalline material A. The content of crystalline material A in the toner is preferably smaller than that of resin M, and a sufficient effect can be obtained with a smaller amount of crystalline material B than that of crystalline material A. XB / XA is more preferably 1 / 15 to 1 / 2, and even more preferably 1 / 11 to 3 / 10.

[0066] The content of the crystalline material B is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 6 parts by mass, and even more preferably 1 to 4 parts by mass, relative to 100 parts by mass of the binder resin. The proportion of the crystalline material B in the total amount of the crystalline materials is preferably 1 to 30% by mass, and more preferably 5 to 15% by mass.

[0067] [About crystalline material C] As described above, the toner further contains crystalline material C in addition to the crystalline materials A and B. The crystalline material C is characterized in that it has low compatibility with the resin M and has better compatibility with the crystalline material B than with the resin M.

[0068] Examples of such crystalline material C include petroleum waxes and derivatives thereof such as paraffin wax, microcrystalline wax, and petrolatum; montan wax and derivatives thereof; hydrocarbon waxes and derivatives thereof produced by the Fischer-Tropsch process; polyolefin waxes and derivatives thereof such as polyethylene wax and polypropylene wax, natural waxes and derivatives thereof such as carnauba wax and candelilla wax; higher aliphatic alcohols; fatty acids such as stearic acid and palmitic acid; acid amide waxes; hydrogenated castor oil and derivatives thereof; vegetable waxes; animal waxes; tetrafunctional ester waxes such as pentaerythritol tetrastearate, pentaerythritol tetrapalmitate, and pentaerythritol tetrabehenate; and hexafunctional ester waxes such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and dipentaerythritol hexabehenate.

[0069] In particular, from the viewpoint of having low compatibility with resin M and relatively high structural similarity to crystalline material B, it is preferable that crystalline material C is at least one selected from the group consisting of hydrocarbon waxes, tetrafunctional ester waxes, and hexafunctional ester waxes.

[0070] The melting point of the crystalline material C is preferably 50°C or more and 100°C or less. When the melting point of the crystalline material C is in the above range, both low-temperature fixability and storage stability of the toner can be achieved. When the melting point of the crystalline material C is 50.0°C or more, the storage stability of the fixed image at high temperatures is improved. Furthermore, when the melting point is 100.0°C or less, sufficient low-temperature fixability can be obtained. The melting point of the crystalline material C is more preferably 60°C or more and 100°C or less, and even more preferably 70.0°C or more and 90.0°C or less. The melting point of the crystalline material C can be controlled by the constituent materials of the crystalline material C. A method for measuring the melting point of the crystalline material C will be described later.

[0071] The crystalline material C preferably has a peak molecular weight (Mp) of o-dichlorobenzene soluble matter of 400 or more and 2000 or less, as measured by high-temperature gel permeation chromatography (GPC). When the peak molecular weight (Mp) is 400 or more, the storage stability of the toner is less likely to decrease. Furthermore, when the peak molecular weight is 2000 or less, the low-temperature fixing property is less likely to decrease. The peak molecular weight (Mp) is more preferably 400 or more and 1000 or less. The method for measuring the peak molecular weight of the crystalline material C will be described later.

[0072] The content of crystalline material C is preferably equal to or less than the content of crystalline material A. This is because crystalline material A acts on resin M, which is the main component of the binder resin, while crystalline material C acts mainly on crystalline material B. The content of crystalline material B in the toner is preferably less than that of resin M, and a sufficient effect can be obtained with a smaller amount of crystalline material C than that of crystalline material A.

[0073] The content of the crystalline material C is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 6 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the binder resin. The proportion of the crystalline material C in the total amount of the crystalline material is preferably 1 to 30% by mass, and even more preferably 5 to 30% by mass.

[0074] [About colorants] The toner particles may contain a colorant. The colorant is not particularly limited, and known colorants such as those shown below can be used. Yellow pigments include yellow iron oxide, Nabels yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, and benzidine yellow. Condensed azo compounds such as Yellow G, Benzidine Yellow GR, Quinoline Yellow Lake, Permanent Yellow NCG, and Tartrazine Lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds are used. Specific examples include the following: CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, and 180. Orange pigments include the following: Permanent Orange GTR, Pyrazolone Orange, Balkan Orange, Benzidine Orange G, Induthrene Brilliant Orange RK, and Induthrene Brilliant Orange GK.

[0075] Examples of red pigments include condensed azo compounds such as red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red C, lake D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, and alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include the following. CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254.

[0076] Examples of blue pigments include alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, copper phthalocyanine compounds such as indanthrene blue BG and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include the following. CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66. Examples of purple pigments include Fast Violet B and Methyl Violet Lake. Examples of green pigments include Pigment Green B and Malachite Green Lake. Examples of white pigments include zinc oxide, titanium oxide, antimony white, and zinc sulfide.

[0077] Examples of black pigments include carbon black, aniline black, non-magnetic ferrite, magnetite, and pigments toned to black using the above yellow, red, and blue colorants. These colorants can be used alone or in mixture, or in the form of a solid solution. If necessary, the colorant may be surface-treated with a substance that does not inhibit polymerization to modify the surface. The content of the colorant is preferably 3.0 parts by mass or more and 20.0 parts by mass or less relative to 100.0 parts by mass of the binder resin or the polymerizable monomer that produces the binder resin.

[0078] [About charge control agents] The toner particles may contain a charge control agent. Any known charge control agent can be used. In particular, a charge control agent that has a high charging speed and can stably maintain a constant charge amount is preferred. Furthermore, when the toner particles are produced by a direct polymerization method, a charge control agent that has low polymerization inhibition properties and is substantially free of solubilized matter in an aqueous medium is particularly preferred. Examples of charge control agents that control the toner particles to be negatively charged include the following.

[0079] Organometallic compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. Other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.

[0080] On the other hand, examples of charge control agents that control toner particles to have a positive charge include the following: nigrosine and nigrosine modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts that are analogues of these, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; and resin-based charge control agents.

[0081] These charge control agents can be used alone or in combination of two or more. The amount of these charge control agents added is preferably 0.01 parts by mass or more and 10.00 parts by mass or less with respect to 100.00 parts by mass of the binder resin.

[0082] [Regarding external additives] The toner particles may be used as they are as a toner, or so-called external additives such as a fluidizing agent and a cleaning aid may be added to the toner particles to improve flowability, chargeability, cleaning properties, etc.

[0083] Examples of the external additive include inorganic oxide fine particles such as silica fine particles, alumina fine particles, and titanium oxide fine particles, inorganic stearic acid compound fine particles such as aluminum stearate fine particles and zinc stearate fine particles, and inorganic titanic acid compound fine particles such as strontium titanate and zinc titanate, etc. These may be used alone or in combination of two or more.

[0084] These inorganic particles are preferably subjected to a gloss treatment using a silane coupling agent, a titanium coupling agent, a higher fatty acid, a silicone oil, etc., to improve heat resistance storage property and environmental stability. The BET specific surface area of ​​the external additive is 10 m 2 / g or more 450m 2 It is preferable that the molecular weight is not more than 1 / g.

[0085] The BET specific surface area can be determined by a low-temperature gas adsorption method using a dynamic constant pressure method according to the BET method (preferably the BET multipoint method). For example, a specific surface area measuring device (product name: Gemini 2375 Ver. 5.0, manufactured by Shimadzu Corporation) is used to adsorb nitrogen gas onto the surface of a sample, and the BET multipoint method is used to measure the BET specific surface area (m2 / g).

[0086] The total amount of these various external additives added is preferably 0.05 parts by mass or more and 5 parts by mass or less, more preferably 0.1 parts by mass or more and 3 parts by mass or less, based on 100 parts by mass of the toner particles. Also, various external additives may be used in combination.

[0087] In order to further improve the storage stability of the fixed image, the toner preferably contains a fatty acid metal salt as an external additive. When a fatty acid metal salt is used as an external additive, the storage stability of the fixed image tends to be further improved. This is presumably because the fatty acid metal salt acts as a crystal nucleating agent for the crystalline material on the image surface after fixing, thereby increasing the crystallinity of the crystalline material on the image surface.

[0088] The fatty acid metal salt is preferably a salt of a fatty acid and at least one metal selected from the group consisting of zinc, calcium, magnesium, aluminum, and lithium. Among them, fatty acid zinc particles are particularly preferred because they have low water absorption. In addition, the fatty acid of the fatty acid metal salt is preferably: A higher fatty acid having 12 to 22 carbon atoms (more preferably 16 to 20) is preferred. Using a fatty acid having 12 or more carbon atoms makes it easier to suppress the generation of free fatty acids. The amount of free fatty acids is preferably 0.20 mass% or less. If the carbon number of the fatty acid is 22 or less, the melting point of the fatty acid metal salt is not too high, and good fixability is easily obtained. As the fatty acid, stearic acid is particularly preferred.

[0089] Examples of fatty acid metal salts include metal stearates such as zinc stearate, calcium stearate, magnesium stearate, aluminum stearate, and lithium stearate, and zinc laurate. Among them, it is preferable to use zinc stearate particles for the above-mentioned reasons. The amount of fatty acid metal salt added to the toner (content of fatty acid metal salt) is preferably 0.01 parts by mass or more and 3.0 parts by mass or less, and more preferably 0.03 parts by mass or more and 0.5 parts by mass or less, relative to 100 parts by mass of toner particles. If the amount added is 0.01 parts by mass or more, the effect of adding the fatty acid metal salt can be obtained. Also, if the amount added is as large as 3.0 parts by mass or less, the deterioration of image quality due to the decrease in toner fluidity is unlikely to occur.

[0090] The volume-based median diameter (D50s) of the fatty acid metal salt is preferably 0.15 μm or more and 1.5 μm or less, and more preferably 0.30 μm or more and 1.5 μm or less.

[0091] <Measurement of the median diameter of fatty acid metal salts> The volume-based median diameter of the fatty acid metal salt used in the present invention is measured in accordance with JIS Z8825-1 (2001), specifically as follows. The measurement device used is a laser diffraction / scattering particle size distribution analyzer "LA-920" (manufactured by HORIBA, Ltd.). The measurement conditions are set and the measurement data is analyzed using the dedicated software "HORIBA LA-920 for Windows (registered trademark) WET (LA-920) Ver. 2.02" that comes with the LA-920. The measurement solvent is ion-exchanged water from which impurities such as solids have been removed in advance.

[0092] The measurement procedure is as follows. (1) Attach the batch type cell holder to the LA-920. (2) A specified amount of ion-exchanged water is placed in a batch cell, and the batch cell is set in the batch cell holder. (3) Stir inside the batch cell using a dedicated stirrer tip. (4) Click the "Refractive Index" button on the "Display Condition Setting" screen and select the file "110A000I" (relative refractive index 1.10). (5) On the "Display Condition Setting" screen, set the particle size standard to the volume standard. (6) After warming up for at least one hour, adjust the optical axis, fine-tune the optical axis, and perform a blank measurement. (7) About 60 ml of ion-exchanged water is placed in a 100 ml flat-bottom glass beaker, and about 0.3 ml of a solution obtained by diluting "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) about 3 times by weight with ion-exchanged water is added as a dispersant. (8) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees, and has an electrical output of 120 W. Place approximately 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank, and add approximately 2 ml of Contaminon N to this tank. (9) The beaker of (7) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous solution in the beaker is maximized. (10) While the aqueous solution in the beaker in (9) is irradiated with ultrasonic waves, about 1 mg of fatty acid metal salt is added little by little to the aqueous solution in the beaker and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. Note that during this process, the fatty acid metal salt may form lumps and float on the surface of the liquid. In this case, the lumps are submerged in the water by shaking the beaker, and ultrasonic dispersion is then continued for 60 seconds. In addition, during ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be between 10°C and 40°C. (11) The aqueous solution in which the fatty acid metal salt prepared in (10) is dispersed is immediately added to the batch cell in small amounts while being careful not to introduce air bubbles, and the transmittance of the tungsten lamp is adjusted to 90% to 95%. Then, the particle size distribution is measured. The 50% cumulative diameter is calculated based on the obtained volume-based particle size distribution data.

[0093] [About the developer] The toner can be used as a magnetic or non-magnetic one-component developer, but may also be mixed with a carrier to be used as a two-component developer. As the carrier, magnetic particles made of known materials such as metals such as iron, ferrite, and magnetite, and alloys of these metals with metals such as aluminum and lead, can be used, and among these, ferrite particles are preferably used. As the carrier, a coated carrier in which the surface of magnetic particles is coated with a coating agent such as resin, or a resin dispersion type carrier in which magnetic fine powder is dispersed in a binder resin may also be used. As the carrier, a carrier having a volume average particle size of 15 μm or more and 100 μm or less is preferable, and a carrier having a volume average particle size of 25 μm or more and 80 μm or less is more preferable.

[0094] [About the manufacturing method of toner particles] The toner particles can be produced by a known production method such as a pulverization method, a suspension polymerization method, an emulsion aggregation method, a dissolution suspension method, etc., and the production method is not particularly limited. The production method of the toner is not particularly limited, but a method including either the following steps (i) or (ii) is preferable.

[0095] (i) A process (suspension polymerization method) of forming particles of a polymerizable monomer composition containing a polymerizable monomer capable of producing a binder resin containing a styrene-acrylic copolymer as resin M, a crystalline material A, a crystalline material B, and, if necessary, other additives such as a crystalline material C, in an aqueous medium, and polymerizing the polymerizable monomer contained in the particles of the polymerizable monomer composition. (ii) A process of forming particles of a resin solution obtained by dissolving or dispersing a binder resin containing a styrene-acrylic copolymer as resin M in an organic solvent, crystalline material A, crystalline material B, and, if necessary, other additives such as crystalline material C, in an aqueous medium, and removing the organic solvent contained in the particles of the resin solution (dissolution suspension method).

[0096] [About amorphous polyester resin] The binder resin preferably contains an amorphous polyester resin in addition to the resin M. The content of the amorphous polyester resin in the binder resin is preferably 1.0% by mass or more and 10.0% by mass or less, and more preferably 2.0% by mass or more and 8.0% by mass or less.

[0097] The amorphous polyester resin may be a known polyester resin.Specific examples include a method of dehydrating and condensing a dibasic acid or its derivative (carboxylic acid halide, ester, acid anhydride) and a dihydric alcohol, and, if necessary, a trivalent or higher polybasic acid or its derivative (carboxylic acid halide, ester, acid anhydride), a monobasic acid, a trivalent or higher alcohol, a monohydric alcohol, etc.

[0098] Examples of dibasic acids include maleic acid, fumaric acid, itaconic acid, oxalic acid, malonic acid, succinic acid, dodecylsuccinic acid, dodecenylsuccinic acid, adipic acid, azelaic acid, and sebacic acid. dibasic acids such as phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, tetrabromophthalic acid, tetrachlorophthalic acid, HET acid, hymic acid, isophthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, etc. Dibasic acid derivatives include carboxylic acid halides, esters, and acid anhydrides of aliphatic and aromatic dibasic acids.

[0099] On the other hand, examples of dihydric alcohols include acyclic aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, and neopentyl glycol; bisphenols such as bisphenol A and bisphenol F; alkylene oxide adducts of bisphenol A such as an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A; and aralkylene glycols such as xylylenediglycol. Examples of trivalent or higher polybasic acids and their anhydrides include trimellitic acid, trimellitic anhydride, pyromellitic acid, and pyromellitic anhydride.

[0100] <Method of measuring peak molecular weight (Mp) and weight average molecular weight (Mw)> The peak molecular weight (Mp) and weight average molecular weight (Mw) of crystalline materials, resins, and toners are measured using gel permeation chromatography (GPC) as follows. First, the sample to be measured is dissolved in tetrahydrofuran (THF) at room temperature. If it is difficult to dissolve, heat it to a temperature of 35°C or less. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is 0.8% by mass. This sample solution is used to perform measurements under the following conditions. Equipment: High-speed GPC equipment "HLC-8220GPC" [Tosoh Corporation] Column: 2 columns of LF-604 [Showa Denko Co., Ltd.] Eluent:THF Flow rate: 0.6mL / min Oven temperature: 40℃ Sample injection volume: 0.020mL

[0101] In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0102] <Melt point measurement method> The melting point of the crystalline material (crystalline resin or wax) is measured using a differential scanning calorimeter (DSC) Q2000 (manufactured by TA Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃

[0103] The melting points of indium and zinc are used to correct the temperature of the detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, about 5 mg of sample is precisely weighed and placed in an aluminum pan, and a measurement is performed once. An empty aluminum pan is used as a reference. The peak temperature of the maximum endothermic peak at that time is taken as the melting point.

[0104] <Measurement of glass transition temperature (Tg)> The glass transition temperature of an amorphous resin is the temperature (°C) at the point where a line equidistant in the vertical direction from a line extending the baseline before and after the onset of a specific heat change intersects with the curve of the stepwise change portion of the glass transition in the reversing heat flow curve, in a reversing heat flow curve during heating obtained by differential scanning calorimetry in the above-mentioned method for measuring the melting point.

[0105] <Identification of the structure, peak molecular weight and melting point of the crystalline material in the toner, and identification of the structure and peak molecular weight of resin M> The structure and composition of the crystalline material in the toner and the resin M were identified and analyzed using a nuclear magnetic resonance ( 1 H-NMR, 13 The analysis can be performed using C-NMR. The apparatus used is described below. Each sample may be collected by separating it from the toner and analyzed. Nuclear magnetic resonance ( 1 H-NMR, 13 C-NMR) Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times accumulated: 64 The peak molecular weight and melting point can be calculated from the specified composition or based on literature values.

[0106] <Measurement of Resin M Content in Binder Resin in Toner> The content of resin M in the binder resin in the toner can be calculated by determining the molar composition ratio from the signal integral ratio (area ratio) in the above NMR measurement. The weight composition ratio is calculated by multiplying the molar composition ratio by the molecular weight of each compound, and the content of resin M can be calculated from the weight composition ratio.

[0107] <Measurement of the content of crystalline materials A, B, and C in toner> The content of crystalline materials A, B, and C in the toner can be calculated by determining the molar composition ratio from the signal integral ratio (area ratio) in the above NMR measurement. The weight composition ratio is calculated by multiplying the molar composition ratio by the molecular weight of each compound, and the content of crystalline materials A, B, and C can be calculated from the weight composition ratio.

[0108] <Method of measuring weight average particle size (D4) of toner> The weight-average particle diameter (D4) of the toner is calculated as follows. The measuring device is a precision particle size distribution measuring device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube. The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.). The measurement is performed with an effective measurement channel count of 25,000. The electrolyte solution used for the measurement is one in which special grade sodium chloride is dissolved in ion-exchanged water to a concentration of approximately 1 mass%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.) can be used.

[0109] Before carrying out measurements and analysis, the dedicated software is configured as follows. On the "Change standard measurement method (SOMME)" screen of the dedicated software, the total count number in control mode is set to 50,000 particles, the number of measurements is set to 1, and the Kd value is set to the value obtained using "standard particle 10.0 μm" (manufactured by Beckman Coulter). The threshold and noise level are automatically set by pressing the "Threshold / Noise Level Measurement Button." In addition, the current is set to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and "Flush aperture tube after measurement" is checked. On the "Change from pulse" screen of the dedicated software, In the "Particle Size Conversion Settings" screen, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.

[0110] (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) About 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a dilution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted about three times by mass with ion-exchanged water is added as a dispersant. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees, and has an electrical output of 120 W. Place approximately 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank, and add approximately 2 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight-average particle size (D4). EXAMPLES

[0111] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is in no way limited thereto. "Parts" used in the examples are by weight unless otherwise specified.

[0112] The names and physical properties of the resin M and crystalline materials used in the examples and comparative examples are shown in Tables 1 and 2. [Table 1]

[0113] In the table, Mw is the weight average molecular weight, and SPm is the solubility parameter (SP value) of resin M. The unit of SP value is (cal / cm 3 ) 1 / 2 It is.

[0114] [Table 2]

[0115] In the table, Tm indicates the melting point, and Mp indicates the peak molecular weight. The unit of the SP value is (cal / cm 3 ) 1 / 2 It is.

[0116] Examples of toner production are shown below: Toners 1 to 41 were produced as examples, and toners 42 to 49 were produced as comparative examples.

[0117] <Production Example of Amorphous Polyester Resin 1> In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube, a dehydration tube, and a pressure reducing device, 1.0 mol of terephthalic acid, 0.65 mol of a propylene oxide 2 mol adduct of bisphenol A, and 0.35 mol of ethylene glycol were added and heated to a temperature of 130°C while stirring. Then, 0.52 parts of tin di(2-ethylhexanoate) was added as an esterification catalyst relative to 100.0 parts of the total amount of the monomers, and the temperature was raised to 200°C, and condensation polymerization was performed until the desired molecular weight was reached. Furthermore, 0.03 mol of trimellitic anhydride was added to obtain amorphous polyester resin 1. The weight average molecular weight (Mw) of the obtained amorphous polyester resin 1 was 6000, the glass transition temperature (Tg) was 49°C, and the acid value was 11.2 mgKOH / g.

[0118] <Toner 1 Manufacturing Example> Styrene 60.0 parts Colorant 6.0 parts (CI Pigment Blue 15:3, Dainichi Seika Chemicals Co., Ltd.) The above materials were placed in an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5 hours to obtain a pigment dispersion liquid. Styrene 15.0 parts n-Butyl acrylate 25.0 parts Amorphous polyester resin 1 5.0 parts ·Crystalline material 2 15.0 parts ·Crystalline material 8 2.0 parts ·Crystalline material 13 4.0 parts Hexanediol diacrylate (HDDA) 0.3 parts

[0119] The above materials were mixed and added to the pigment dispersion. The resulting mixture was kept at 60°C and stirred at 500 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to dissolve and disperse uniformly, preparing a polymerizable monomer composition. Meanwhile, in a container equipped with a high-speed stirring device Clearmix (manufactured by M Technique Co., Ltd.), 850.0 parts of 0.10 mol / L-Na3PO4 aqueous solution and 8.0 parts of 10% hydrochloric acid were added, the rotation speed was adjusted to 15,000 rpm, and the mixture was heated to 70°C. 68.0 parts of 1.0 mol / L-CaCl2 aqueous solution were added to this to prepare an aqueous medium containing a calcium phosphate compound.

[0120] After the polymerizable monomer composition was added to the aqueous medium, 9.0 parts of t-butyl peroxypivalate, a polymerization initiator, was added, and the mixture was granulated for 10 minutes while maintaining a rotation speed of 15,000 rpm. After that, the agitator was changed from the high-speed agitator to a propeller agitator, and the mixture was reacted at 70° C. for 5 hours while refluxing, and then the liquid temperature was increased to 85° C. and the mixture was reacted for another 2 hours. After the polymerization reaction was completed, the obtained slurry was cooled, a part was taken out, and the particle size distribution was measured. Furthermore, hydrochloric acid was added to the slurry to adjust the pH to 1.4, and the mixture was stirred for 1 hour to dissolve the calcium phosphate salt. After that, the mixture was washed with water three times the amount of the slurry, filtered, dried, and then classified to obtain toner particles containing resin M1 as a binder resin. The molecular weight distribution of the toner particles was measured, and the weight average molecular weight Mw was calculated to be 30,000.

[0121] Then, dimethyl silicone oil was added as an external additive to 100.0 parts of toner particles. (20% by mass) silica fine particles (number average particle size of primary particles: 10 nm, BET specific surface area: 170 m 2 The mixture was mixed for 15 minutes at 3000 rpm using a Mitsui Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 1.

[0122] <Toner 2-35 Manufacturing Example> As shown in Table 3, toners 2 to 35 were obtained in the same manner as in the production example of toner 1, except that the types and amounts of crystalline materials A, B and C and the type and amount of binder resin M were changed.

[0123] <Toner 36 Manufacturing Example> Styrene 60.0 parts Colorant 6.0 parts (CI Pigment Blue 15:3, Dainichi Seika Chemicals Co., Ltd.) The above materials were placed in an attritor (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5 hours to obtain a pigment dispersion liquid. Styrene 15.0 parts n-Butyl acrylate 25.0 parts Amorphous polyester resin 1 5.0 parts Low molecular weight polystyrene resin 20.0 parts (Mw=3,000, Mn=1,050, Tg=55℃) ·Crystalline material 2 15.0 parts ·Crystalline material 11 2.0 parts ·Crystalline material 13 4.0 parts Hexanediol diacrylate (HDDA) 0.3 parts The above materials were mixed and added to the pigment dispersion liquid. After that, the same procedure as in the production example of toner 1 was carried out to obtain toner 36.

[0124] <Toner 37 Manufacturing Example> Toner 37 was obtained in the same manner as in the production example of toner 36, except that the amount of low molecular weight polystyrene resin added was changed to 25.0 parts.

[0125] <Production Example of Toner 38> Toner 38 was obtained in the same manner as in the production example of toner 36, except that the amount of low molecular weight polystyrene resin added was changed to 38.0 parts.

[0126] <Toner 39 Manufacturing Example> In the manufacturing example of toner 5, silica fine particles (number average particle diameter of primary particles: 10 nm, BET specific surface area: 170 m) that had been hydrophobized with dimethyl silicone oil (20% by mass) were used as an external additive. 2 Toner 39 was obtained in the same manner as Toner 5, except that 2.0 parts of toner particle diameter (volume-based median diameter D50s: 0.3 μm) and 0.5 parts of zinc stearate particles (volume-based median diameter D50s: 0.3 μm) were used.

[0127] <Toner 40 Manufacturing Example> In the manufacturing example of toner 5, silica fine particles (number average particle diameter of primary particles: 10 nm, BET specific surface area: 170 m) that had been hydrophobized with dimethyl silicone oil (20% by mass) were used as an external additive. 2Toner 40 was obtained in the same manner as Toner 5, except that 2.0 parts of toner particle diameter (volume-based median diameter D50s: 1.5 μm) and 0.05 parts of zinc stearate particles (volume-based median diameter D50s: 1.5 μm) were used.

[0128] <Production Example of Toner 41> Toner 41 was obtained in the same manner as in the production example of toner 5, except that zinc stearate particles were not used as the external additive.

[0129] [Table 3] In the table, "M amount" indicates the content (mass %) of resin M in the binder resin.

[0130] <Production Example of Toner 42-49> As shown in Table 3, toners 42 to 49 were obtained in the same manner as in the production example of toner 1, except that the types and amounts of crystalline materials A, B, and C, and the type and amount of binder resin M were changed. Table 4 shows the ratios (mass%) of each of crystalline materials A, B, and C to the total amount of crystalline materials in toners 1 to 49.

[0131] [Table 4]

[0132] <Examples 1 to 41 and Comparative Examples 1 to 8> The performance of the obtained toners 1 to 49 was evaluated according to the following method. The results are shown in Tables 5 and 6. Examples 19, 20, 24 and 33 were evaluated as reference examples.

[0133] [Table 5]

[0134] [Table 6]

[0135] [Low temperature fixability] The evaluation of low-temperature fixability was carried out as follows. A color laser printer (HP Color LaserJet Enterprise Color M751dn, manufactured by HP) with the fixing unit removed was prepared, the toner was removed from the cyan cartridge, and the toner to be evaluated was replaced. Next, a receiving paper (HP Laser Jet90, manufactured by HP, 90 g / m 2 ) using the filled toner, an unfixed toner image of 2.0 cm length x 5.0 cm width (toner loading amount: 0.45 mg / cm 2 ) was formed at a position 1.0 cm from the upper end in the paper feed direction. Next, the removed fixing unit was modified so that the fixing temperature could be adjusted, and a fixing test of an unfixed image was carried out using this.

[0136] Under normal temperature and humidity conditions (23°C, 60% RH), the initial temperature was 100°C, and the set temperature was raised in increments of 10°C, while fixing the unfixed image at each temperature. The fixed image was left to stand for one day under normal temperature and humidity conditions (temperature 23°C, relative humidity 60%), after which the image gloss of the fixed image was measured to evaluate low-temperature fixability. A handy gloss meter PG-1 (manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the image gloss. The measurement conditions were set to a projection angle and a receiving angle of 75°, and measurements were taken at five different points on the fixed image, and the average value was taken as the initial gloss value after fixing. The lowest fixing temperature at which the gloss of the fixed image exceeded 60 was taken as the fixing temperature.

[0137] [Image gloss stability] The print image at the lowest fixing temperature in the above low-temperature fixing test was left to stand for 1 day, 3 days, or 2 weeks in an environment of 50°C and 30%, and then left to stand for 1 day in an environment of normal temperature and humidity (temperature 23°C, relative humidity 60%). Then, the image gloss was measured and compared with the initial gloss value after fixing. The image gloss stability was evaluated according to the following criteria. A: Image gloss change range is 3 or less B: Image gloss change range is more than 3 and less than 6 C: Image gloss change range is more than 6 and less than 10 D: Image gloss change range is more than 10 and 15 or less E: Image gloss change range is greater than 15

[0138] In Examples 1 to 41, good results were obtained in all the evaluation items. On the other hand, in Comparative Examples 1 to 8, results were inferior to those of the Examples in all the above evaluation items. From the above results, according to the present disclosure, it is possible to obtain a toner that has excellent low-temperature fixing properties and suppresses gloss changes over time in printed images.

Claims

1. A toner having toner particles containing a binder resin, a crystalline material A, a crystalline material B, and a crystalline material C, The binder resin contains 70% by mass or more of resin M based on the mass of the binder resin, The melting point of the crystalline material A is 50.0° C. or more and 100.0° C. or less, the content of the crystalline material A relative to the total amount of the crystalline materials in the toner is 56% by mass or more; The absolute value of the SP value difference between the resin M and the crystalline material A is ΔSPAM (cal / cm 3 ) 1 / 2, The absolute value of the SP value difference between the resin M and the crystalline material B is ΔSPBM (cal / cm 3 ) 1 / 2, The absolute value of the SP value difference between the resin M and the crystalline material C is ΔSPCM (cal / cm 3 ) 1 / 2 , The absolute value of the SP value difference between the crystalline material A and the crystalline material B is ΔSPAB (cal / cm 3 ) 1 / 2, When the peak molecular weight Mp of the crystalline material A is MpA, the peak molecular weight Mp of the crystalline material B is MpB, and the peak molecular weight Mp of the crystalline material C is MpC, A toner characterized by satisfying the following formulas (1) to (5): 50≦MpB×ΔSPBM 2 -MpA×ΔSPAM 2 ≦450 ・・・(1) MpA×ΔSPAM 2 ≦800 ・・・(2) ΔSPAB≦0.26 (3) 0<MpC×ΔSPCM 2 −MpB×ΔSPBM 2 (4) 800<MpC × ΔSPCM 2 ... (5)

2. 2. The toner according to claim 1, wherein the crystalline material C is at least one selected from the group consisting of a hydrocarbon wax, a tetrafunctional ester wax, and a hexafunctional ester wax.

3. 3. The toner according to claim 1, wherein when an absolute value of the SP value difference between the crystalline material A and the crystalline material C is ΔSPAC (cal / cm3) 1 / 2 and an absolute value of the SP value difference between the crystalline material B and the crystalline material C is ΔSPBC (cal / cm3) 1 / 2, the following formula (7) is satisfied: 0 < ΔSPAC-ΔSPBC (7)

4. The toner according to any one of claims 1 to 3, wherein when a content of the crystalline material A in the toner is XA (mass%) and a content of the crystalline material B in the toner is XB (mass%), the following formula (8) is satisfied: XA-XB>0...(8)

5. 5. The toner according to claim 1, wherein the crystalline material B is a condensate of an aliphatic dicarboxylic acid having 2 to 10 carbon atoms and an aliphatic monoalcohol having 14 to 24 carbon atoms.

6. 6. The toner according to claim 1, wherein the crystalline material A is a condensation product of an aliphatic diol having 2 to 10 carbon atoms and an aliphatic monocarboxylic acid having 14 to 24 carbon atoms.

7. 7. The toner according to claim 1, further comprising a fatty acid metal salt as an external additive.

8. The resin M is a vinyl resin, the crystalline material A is a condensate of an aliphatic diol having 2 to 10 carbon atoms and an aliphatic monocarboxylic acid having 14 to 24 carbon atoms, the crystalline material B is a condensate of an aliphatic dicarboxylic acid having 2 to 10 carbon atoms and an aliphatic monoalcohol having 14 to 24 carbon atoms, 8. The toner according to claim 1, wherein the crystalline material C is at least one selected from the group consisting of a hydrocarbon wax, a tetrafunctional ester wax, and a hexafunctional ester wax.

9. A toner described in any one of claims 1 to 8, wherein the content of crystalline material A relative to the total amount of crystalline materials in the toner is 90 mass % or less.

Citation Information

Patent Citations

  • Toner for developing electrostatic charge image

    JP1998133412A

  • toner

    JP2010145552A

  • toner

    JP2010145553A

  • Toner for electrostatic charge image development

    JP2013105128A

  • Toner

    JP2017044980A